2019
DOI: 10.1257/aer.20181714
|View full text |Cite
|
Sign up to set email alerts
|

Incentivized Resume Rating: Eliciting Employer Preferences without Deception

Abstract: We introduce a new experimental paradigm to evaluate employer preferences, called incentivized resume rating (IRR). Employers evaluate resumes they know to be hypothetical in order to be matched with real job seekers, preserving incentives while avoiding the deception necessary in audit studies. We deploy IRR with employers recruiting college seniors from a prestigious school, randomizing human capital characteristics and demographics of hypothetical candidates. We measure both employer preferences for candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…We find that both interventions improve the quality of the applicant pool in the eyes of local firm managers. We show this result in Table 6 using a series of linear probability 47 Kessler et al (2019) propose a similar methodology -called Incentivised Resume Rating -to elicit employer preferences. There are two main di erence between their methodology and ours: (i) they use fictitious CVs while we rely on real CVs, and (ii) in their design, employers assess CVs by reporting a cardinal score, while in our design employers report a rank.…”
Section: Via Do Managers Value Cognitive Ability and Are They Aware Of The Benefits Of Application Incentives?mentioning
confidence: 99%
“…We find that both interventions improve the quality of the applicant pool in the eyes of local firm managers. We show this result in Table 6 using a series of linear probability 47 Kessler et al (2019) propose a similar methodology -called Incentivised Resume Rating -to elicit employer preferences. There are two main di erence between their methodology and ours: (i) they use fictitious CVs while we rely on real CVs, and (ii) in their design, employers assess CVs by reporting a cardinal score, while in our design employers report a rank.…”
Section: Via Do Managers Value Cognitive Ability and Are They Aware Of The Benefits Of Application Incentives?mentioning
confidence: 99%
“…In terms of the former, perhaps the most prominent general finding is that people evaluate the performance of men versus women differently and in accordance with stereotypic expectations. For example, a recent field experiment showed that employers recruiting in Science, Technology, Engineering and Mathematics (STEM) fields evaluate a woman with a 4.0 GPA equally as a White man with a 3.75 GPA and place less importance on a prestigious internship when the job candidate is a woman rather than a man (Kessler et al, 2019). Similarly, experimental studies in the lab found that identical resumes elicit different call-back and job offer rates depending on the gender of the applicant (Moss-Racusin et al, 2012).…”
mentioning
confidence: 99%
“…We show this using an incentivized choice experiment with the sample of 69 establishments described in the previous subsection. We ask the person at each establishment responsible for hiring to rank profiles of seven hypothetical candidates and tell them we will use their ranking to match them with workseekers from the online database, following Kessler et al (2019). Six of the profiles have middle terciles for five assessments, and a top tercile for one assessment.…”
Section: Certification Facilitates Horizontal More Than Vertical Differentiationmentioning
confidence: 99%